Avaliação do estresse térmico em búfalas Murrah criadas em dois diferentes sistemas de manejo nas condições climáticas da amazônia oriental - Silva, Jamile Andréa Rodrigues da (2010)
This thesis aimed at evaluate the effects of heat stress on physiological, hematologic and hormonal responses of female buffaloes raised under full sun and shade at Embrapa Eastern Amazon, Belem, Para State, Brazil (01°.26’.03” S e 48°.26’.03” W). Twenty female Murrah buffaloes were used. They were randomly assigned into two groups (Non Shade Group – NS, and Shade Group – SG). All animals were kept under rotational grazing: the ones in the NS group (n=10) were maintained in paddocks under a silvopastoral system, shaded by the tree legume Acacia mangium, whereas the ones in the SG (n=10) were kept in paddocks with no shade access. All animals were grass fed with Brachiaria humidicola, and had free access to drinking water and mineral salt. The climate variables: air temperature (AT), relative humidity (RH) and black globe temperature (BGT) were measured on each treatment. The physiological variables studied were: rectal temperature (RT), respiratory rate (RR), heart rate (HR) and body surface temperature (BST). They were measured in the morning (7h00) and in the afternoon (13h00). Blood sampling, aiming erythrogram, leukocyte count, and the quantitative determination of cortisol, triiodothyronine (T3) and thyroxine (T4), was carried out at the time of the highest temperature in the region (13h00). Three distinct climatic periods of the year were considered: rainy (January to April), transition (May to July) and less rainy (August to December). Analysis of variance showed that there were significant differences (P<0.05) in the AT, temperature humidity index (THI), and black globe humidity index (BGHI) between the distinct periods of the day and between groups. The highest rates were observed in the afternoon in the NS group. The highest RH values were observed during the rainy period. There were statistical differences (P<0.05) in RH between the periods of the day, and the highest values were measured in the morning. Results of analysis of variance for the physiological parameters RT, BST, RR and HR revealed that there were significant differences between the periods of the day and groups, and the values observed in group SS, during the afternoon, were higher (P<0.05) than the ones during the morning. Regarding the hematologic data, the leukocytes count was influenced by the periods of the year and treatments (P<0.05). During the rainy periods, the SG group presented the highest values. In the less rainy and transition periods, the highest values were observed in the NS group. The erythrocytes count was influenced (P<0.05) by the treatments, and the NS group showed the highest values in the less rainy period. Hemoglobin contents were not influenced by the treatments, however they were influenced by the periods of the year, and the highest levels (P <0.05) were observed during the transition and less rainy periods. Regarding the hormones, cortisol was influenced by the treatments (P<0.05), and the NS group showed the highest values. The highest mean rates of cortisol were reported during the rainy and less rainy periods of the year (P<0.05), and the transition period presented the lowest cortisol values. The highest average levels of T3 and T4 were recorded during the rainy period (P<0.05). RT, BST and RR presented a significant and positive (P<0.01) correlation with AT, THI and BGHI, and a negative correlation with RH. These correlations were higher during the less rainy period. HR showed low, but relevant and positive (P<0.01) correlations with AT, THI and BGHI during the two other periods, and significant and negative (P<0.05) correlation with RH only in the rainy period. Leukocytes, erythrocytes and the globular volume did not correlate with AT, RH and BGHI. Only hemoglobin presented a significant and negative (P<0.05) correlation with RH. Cortisol did not correlate with AT, RH and BGHI. T3 and T4 correlated negatively with AT and BGHI, and positively with RH. We concluded that regardless of the season, Murrah buffaloes are subject to a hostile environment, and that the less rainy period is the most conducive to cause heat stress. The transition period caused less impact on the hormonal variables. It can be considered as the period with the best thermal comfort. Forestation of pasture areas is sufficient to increase comfort and consequently improve the productive performance of the animals, especially during the afternoon.